2017
DOI: 10.3390/f8070260
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Adoption of Alley Cropping as a Climate-Smart Agriculture Practice: Lessons from Maize Cultivation among the Maya in Southern Belize

Abstract: Climate-smart agriculture (CSA) is proposed as a necessity, as the agricultural sector will need to adapt to resist future climatic change, to which high emissions from the sector contribute significantly. This study, which is an exploratory case study based on qualitative interviews and field observations, investigates the barriers to making a CSA-adjustment in maize production among Maya communities in southern Belize. The adjustment is alley cropping, which is a low-input adjustment that has the potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The empirical studies we reviewed described the potentially large role of the environmental and management context in affecting adaptation and mitigation outcomes-and thus the capacity of a practice to provide synergistic outcomes. For example, studies that empirically assessed adaptation and mitigation outcomes found that GHG emissions could be higher if some 'climate-smart' agricultural practices, like alley cropping [62] or intermittent drainage [61], were not implemented appropriately e.g. were applied in less favourable environmental or management contexts.…”
Section: Environmental and Management Contextmentioning
confidence: 99%
“…The empirical studies we reviewed described the potentially large role of the environmental and management context in affecting adaptation and mitigation outcomes-and thus the capacity of a practice to provide synergistic outcomes. For example, studies that empirically assessed adaptation and mitigation outcomes found that GHG emissions could be higher if some 'climate-smart' agricultural practices, like alley cropping [62] or intermittent drainage [61], were not implemented appropriately e.g. were applied in less favourable environmental or management contexts.…”
Section: Environmental and Management Contextmentioning
confidence: 99%
“…Examples of CSA practices already proposed or being practiced on a small-scale in southern Belize include mulching and soil nutrient enrichment. Adopting CSA in Belize practices can enhance small farmers' adaptation to climate change and sustainably mitigate climate change impacts and support food security under a changing climate (FAO, 2013;Hellin & Fisher, 2019;Kongsager, 2017;Mugambiwa & Tirivangasi, 2017).…”
Section: Planetary Benefits Of Climate-smart Practices On Milpa Farms In Belizementioning
confidence: 99%
“…Hence, public policies should not only provide specific individual incentives to adaptation, but also provide incentives to construct networks, systems of innovation and institutional arrangements that aim to create a favorable environment. It has been acknowledged that the ability of society to confront CC and reduce the vulnerability of agro-socio-economic systems will depend on the adaptive capacity of its stakeholders, as politics are embedded in a society facing environmental challenges [126,127,[144][145][146].…”
Section: Economic and Social Impact And Farmer Adaptationmentioning
confidence: 99%